SWOT analysis on veterinary telemedicine from pet owner and expert perspectives—a mixed-methods survey and interview study in Germany - Karsch, Charline; Tipold, Andrea; Kleinsorgen, Christin (Frontiers in Veterinary Science, 2026)
IntroductionTelemedicine is becoming relevant for veterinarians and pet owners alike. It is insufficient to merely consider the technical requirements. Acceptance, practical applicability and actual user demand are equally important. This research study explores the potential for telemedicine services in small animal practices, examining the perspectives of pet owners and veterinary experts.MethodsA parallel mixed-method design was conducted, comprising a survey of 404 pet owners and interviews with veterinary experts. The primary objective of the study was to explore whether consumers would find an expanded range of telemedicine services appealing and to evaluate the (dis-)advantages of digital veterinary services with respect to animal welfare and owner satisfaction. Additionally, the role of digital services and a first overview of the willingness to pay for these were investigated.ResultsThe survey indicated that digital forms of communication are frequently utilised to contact veterinary practices. Conversely, audiovisual formats play a minor role. Veterinarians and pet-owners appreciate time savings, flexibility and stress reduction for animals as advantages. The lack of physical examination and technical hurdles are considered the main disadvantages. The willingness to pay for healthcare services is influenced by the format: video consultations are more likely to be accepted, while text-based services are often expected to be free. Expert interviews served to broaden the scope of discussion, offering insights into the practical implementation of telemedicine methodologies. SWOT analysis revealed that primary strengths of veterinary telemedicine are time savings, flexibility and stress reduction for both animals and their owners.DiscussionThis digitalisation is regarded as a potential catalyst for enhancing access to and quality of veterinary care, particularly in regions characterised by structural deficiencies or for cases that necessitate specialists´ expertise. Conversely, the following limitations must be acknowledged: firstly, absence of physical examinations; secondly, presence of technical challenges; thirdly, occasional inadequacy of digital competencies. Risks associated with telemedicine include legal uncertainties, data protection concerns and the potential weakening of the personal veterinarian-client relationship due to external providers. Achieving sustainable integration necessitates the establishment of clear legal requirements, technical standards and educational initiatives. These measures are crucial for fostering trust and ensuring the effective incorporation of telemedicine into routine clinical practice.